PENGEMBANGAN MODEL PEMBELAJARAN DIGITAL LITERASI “SCIENCE” MELALUI PENDEKATAN SAINTIFIK BERBASIS PROYEK PADA PEMBELAJARAN IPA DI SMP - Posumah, Irvanda; Taunaumang, Heinrich; Rengkuan, Mariana (Journal of Higher Education and Academic Advancement, 2024)
The primary characteristics of 21st-century learning emphasize the importance of digital literacy in preparing individuals to manage information, collaborate, and adapt to rapid changes in the digital society. A project-based digital literacy learning model is crucial as it equips students with necessary skills to navigate effectively in an increasingly interconnected digital world through authentic projects integrating digital technology, enabling them to learn, innovate, collaborate, and communicate effectively in a continually evolving global context. This development study aims to produce a valid, practical, and effective "SCIENCE" Digital Literacy Learning Model based on project approaches. The research method employed is the 4D R&D model (Define, Design, Development, Dissemination). This study was conducted at SMP Advent 5 Kairagi Weru, Grade VIII, Second Semester of the Academic Year 2023/2024. Research instruments used include interviews, observations, questionnaire surveys, and achievement tests. Data analysis techniques utilized descriptive statistics. Based on the research findings, the validity test results of the project-based "SCIENCE" digital literacy learning model were categorized as valid with a percentage of 88.89%. Practicality assessment based on teacher questionnaire responses indicated a very practical category with a percentage of 91.67%, while student questionnaire analysis also indicated a very practical category with a percentage of 94.46%. The effectiveness test results were categorized as highly effective with a percentage of 88%. In conclusion, it can be inferred that the "SCIENCE" Digital Literacy Learning Model meets the criteria of being valid, practical, and effective.